SUPPLEMENTATION OF NITROGEN AND POTASSIUM NUTRIENTS THROUGH FOLIAR NUTRITION TO BIDI TOBACCO (Nicotiana tabacum L.) - K. PRABHAKAR (The Journal of Research ANGRAU, 2016)
Field experiment was conducted for two kharif seasons (2014 – 15 and 2015 – 16) at Regional Agricultural Research Station, Nandyal to study the response of bidi tobacco to supplemental nitrogen (N) and potassium (K) nutrients through foliar application. The treatments consisted of ten treatment combinations from three sources of nutrients (i.e. potassium nitrate (KNO3), ammonium sulphate + sulphate of potash and urea + sulphate of potash) and three intervals of foliar sprays at 45 days after sowing (DAT), 60 DAT, 45 and 60 DAT. The experiment was laid out in a RBD design and replicated thrice. Foliar nutrition of 2.5% potassium nitrate twice at 45 and 60 DAT recorded significantly higher cured leaf yield (1783 kg ha-1) but at par with foliar nutrition of 2.5% Ammonium sulphate + sulphate of potash twice at 45 and 60 DAT (1743 kg ha-1). Control treatment (without foliar nutrition) recorded significantly lower cured leaf yield of 1520 kg ha-1. Foliar nutrition of N and K recorded positive effect on content of nitrogen and potassium in cured leaf. The quality parameters viz., nicotine, reducing sugars and chlorides in cured leaf were not altered by the foliar nutrition of N and K compared to control. However, higher net returns were recorded with foliar nutrition of 2.5% ammonium sulphate + sulphate of potash twice at 45 and 60 DAT (Rs. 80169/- per ha) followed by application of 2.5% potassium nitrate (KNO3) (Rs. 69645/- ha-1) whereas without foliar spray treatment recorded the lowest net returns of Rs. 67550/- ha-1.